Experimental assessment and numerical modeling of the nonlinear behavior of the masonry shear walls under in-plane cyclic loading considering the brickwork-setting effect - Amir Hossein Karimi (Iranian Society of Structrual Engineering (ISSE), 2017)
In this article, the main purpose is nonlinear analysis of the cyclic behavior of the masonry shear walls including brickwork setting using finite element method. Three different brickwork-settings including running bond style, herringbone style and Zarbi style (herreh style) were investigated. To this end, the walls (in dimension of 195×1500×1720 mm) were tested in the laboratory and then were simulated using macro modeling method by Abaqus software, and their hysteretic curves was drawn. The concrete damaged plasticity criteria in the Abaqus software is a model used in this research.In this method, the main failure mechanisms of fracture are cracking in tension and crushing in compression. The macro modeling method was used for numerical assessment of the masonry walls. After numerical modeling and drawing hysteretic curves and contrasting them with laboratory results, it was proven that the concrete damaged plasticity model, which is behavioral model for simulating concrete material, can be used for modeling masonry materials under seismic loading. However, this model cannot be used to simulate pinching effect in hysteretic curve drawn from seismic loading. The envelope curve resulted from the numerical analysis of all three brickwork layouts had a good agreement with the results of the laboratory tests, but in Hysteretic curve of Herringbone style and Zarbi style the pinching effect did not match experimental results